Universal Design: a valuable resource to enhance and improve teaching and learning - Caoimhe Kiernan (Irish Journal of Academic Practice)
Opinion Piece. This short piece will explore my experience of undertaking the Digital Badge for Universal Design in Teaching and Learning with the National Forum for the Enhancement of Teaching and Learning from October to December 2022.